Investigating the factors of brand loyalty in e-commerce through brand engagement and brand switching behavior - Have, Renske Marije Ten (2023)
This study examines the influence of customer characteristics on brand loyalty within the Fast-Moving-Consumer-Goods (FMCG) industry's online environment. As omnichannel shopping gains prominence, online brand loyalty research lags, neglecting the impact of this shift on consumer behavior. Previous studies vary in their brand loyalty measurement approaches, some emphasizing repeat purchases, while others assess cognitive, affective, and behavioral aspects. To address this, this study combines Hollebeek's Customer Brand Engagement (CBE) scale and Liao's Push-Pull-Mooring (PPM) model of brand switching behavior (BSB). The relationship between customer attributes (age, gender, education, income, residence type, nationality) and brand loyalty using the CBE and BSB scales is examined. Gathering 230 valid responses through an online questionnaire, the study reveals that consumers engage more emotionally and actively with brands rather than cognitively. Findings indicate that factors such as youth, income, and the type of residence influence brand engagement and subsequently, brand loyalty. Contradicting to previous research, no significant relation between the CBE and BSB scores are found, implying a disconnect between brand engagement and brand switching behavior. Despite engagement, consumers still exhibit brand switching tendencies. This study contributes to understanding online brand loyalty in the FMCG industry, underscoring the importance of emotional connections and engagement in fostering loyalty. It also calls for further exploration of evolving consumer behavior in the omnichannel shopping landscape.